MEDICAL AND NURSING STUDENTS’ ATTITUDES TOWARD INDIVIDUALS WITH INTELLECTUAL DISABILITIES - literature review - Glamočak, Sandra; Uzelac, Jovana; Aranđelović, Branimirka (Medicinski časopis, 2024)
ABSTRACT:Parallel to the deinstitutionalization process, there has been a paradigm shift in the approach to individuals with intellectual disabilities (ID), emphasizing the integration of this population into the community. Despite these promising changes, individuals with ID continue to experience concerning levels of discrimination within the healthcare system. From the perspective of students training to become professional medical personnel, understanding their attitudes towards providing healthcare services to individuals with ID is critically important, especially as basic healthcare services are increasingly expected to meet the health needs of individuals with ID. The aim of this paper is to review the literature to identify the factors that influence the formation of medical and nursing students' attitudes towards individuals with ID. Data from the literature were collected using PubMed, KoBSON, and Google Scholar databases. Access was provided to free full texts in both English and Serbian. Based on the review of research results, it is possible to identify a range of different factors that have both positive and negative influences on the formation of medical and nursing students' attitudes towards individuals with ID. Some of these factors include: gender, year of study, previous experience with individuals with ID, and prior knowledge about this population. Considering the attitudes of medical and nursing students towards individuals with ID is significant, as their attitudes will greatly shape the approach to healthcare for this population. Furthermore, the attitudes of future healthcare professionals can be a key factor in creating or mitigating inequalities in the healthcare system for individuals with ID.Keywords: attitudes, medical students, nursing students, individuals with intellectual disabilities,  healthcare